Metode A New Additive Ratio Assessment (ARAS) Dalam Penentuan Pegawai Honor Berprestasi - Badiwibowo Atim, Sandi; Arundaa, Rillya (PT. Tech Cart Press, 2024)
The determination of outstanding honor employees is not only a form of recognition for outstanding performance, but also a motivator to encourage professional growth and individual empowerment in the work environment. This study aims to apply the ARAS method in determining outstanding honor employees so that the results of recommendations become considerations for leaders in determining outstanding honor employees. This study aims to apply the ARAS method in determining outstanding honor employees so that the results of recommendations become considerations for leaders in determining outstanding honor employees. The ranking results show the results of rank 1 with the final value of the ARAS method of 0.9915 obtained by the name of employee B, rank 2 with the final value of the ARAS method of 0.985 obtained by the name of employee D, rank 3 with the final value of the ARAS method of 0.924 obtained by the name of employee A.